2010
DOI: 10.1016/j.febslet.2010.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Tudor‐SN interacts with and co‐localizes with G3BP in stress granules under stress conditions

Abstract: a b s t r a c tSGs are mRNA containing cytoplasmic structures that are assembled in response to stress. Tudor-SN protein is a ubiquitously expressed protein. Here, Tudor-SN protein was found to physiologically interact with G3BP, which is the marker and effector of SG. The kinetics of the assembly of SGs in the living cells demonstrated that Tudor-SN co-localizes with G3BP and is recruited to the same SGs in response to different stress stimuli. Knockdown of endogenous Tudor-SN did not inhibit the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 31 publications
7
83
0
Order By: Relevance
“…Biochemical approaches demonstrated that SND1 is a cleavage substrate for caspase 3 and that inhibition of this cleavage reduces the overall efficiency of the programmed cell death process (27). Further implicating SND1 in cellular stress response programs, it was recently shown that SND1 interacts with the stress granule marker G3BP and that the two proteins strongly co-localize to stress granules upon induction of various cellular stresses (54).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical approaches demonstrated that SND1 is a cleavage substrate for caspase 3 and that inhibition of this cleavage reduces the overall efficiency of the programmed cell death process (27). Further implicating SND1 in cellular stress response programs, it was recently shown that SND1 interacts with the stress granule marker G3BP and that the two proteins strongly co-localize to stress granules upon induction of various cellular stresses (54).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether SND1 regulated the expression of IGFBP3 protein by direct interaction, we executed Co-IP experiment with SND1 antibody. Although we detected the presence of G3BP, which is a known partner of SND1 (Gao et al, 2010) in the precipitations, we failed to observe the existence of IGFBP3 (Fig. 5C).…”
Section: Snd1 Affects Igfbp3 Expression In Smmc-7721 Cellsmentioning
confidence: 65%
“…SND1 has a Tudor homology domain and five repeated staphylococcal nuclease homology domains (Callebaut and Mornon, 1997) suggested to act as interaction platforms for proteins and RNAs, respectively (Shaw et al, 2007;Li et al, 2008). SND1 has been implicated in a variety of cellular processes such as transcription (Tong et al, 1995;Dash et al, 1996;Leverson et al, 1998;Wang et al, 2010), RNA splicing Gao et al, 2012) and RNA metabolism (Gao et al, 2010). SND1 has also been reported as one of the components of the RNA-induced silencing complex (RISC), which mediates gene silencing (Caudy et al, 2003).…”
mentioning
confidence: 99%
“…21 Notably, human TSN interacts with ADAR1, RNA-binding Ras-GAP SH3 binding protein (G3BP) and with several core components of stress granules (SGs) under stress conditions, whereupon SN domains are essential for both interaction and SG-specific localization of TSN ( Figure 2 and Table 1). 3,11,22 Apart from binding cytoplasmic partners, SN domains of mammalian TSN bind several components of basal transcription machinery in the nucleus ( Figure 2). All these findings suggest that TSN, through its SN domains, may participate in both transcriptional and post-transcriptional regulation of gene expression.…”
Section: Structure and Intracellular Localization Of Tsn: Clues To Mumentioning
confidence: 99%